The Impact Of The Montessori Method On The Socio-Emotional Development Of Children Aged 4-6 Years At Kindy House Kindergarten - Kurniawati, Nunik; Darmiany; Ida Ermiana (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2026)
Early childhood social-emotional development is crucial but often suboptimal in Indonesian early childhood education (PAUD) due to excessive academic priorities. This study aims to analyze the impact of the Montessori method on the social-emotional development of children aged 4-6 years at Kindy House Kindergarten based on STTPA. Using a qualitative descriptive case study approach, the population was children aged 4-6 years at the kindergarten; a purposive sample of 52 active children and 8 teachers. Instruments included STTPA observation guidelines, semi-structured interviews, and documentation; inductive analysis with thematic triangulation. Observation results showed high achievement: self-awareness 91.8%, responsibility 87.6%, prosocial 91.6%, with >80% success indicators. The conclusion states that the Montessori method is effective in developing independence, emotional regulation, and empathy through a structured environment, recommending its widespread adoption in PAUD for optimal STTPA.